Sheepskin in Gunpowder Preservation in the Ottoman Empire - Orhankazi, Sibel; Çomçalı, Selahattin (Fırat University, 2026)
The Ottoman Empire made great efforts to meet the logistical needs of the army, to produce resources for military needs and to protect existing resources. In this context, gunpowder, which is an important element of the Ottoman defense system, and the gunpowder houses necessary for the preservation of gunpowder are of great importance. Sheepskin, with its various uses in the Ottoman Empire, attracts attention especially in the preservation of gunpowder. In addition, it was also used to make ships more durable, to protect and bind documents in state correspondence, and to make items in daily life. However, the production of sheepskin leather was a laborious process and it was only produced in centralized regions and supplied as needed for a certain price. The aim of this study is to examine the place of sheepskin in particular and sheepskin in general in the Ottoman Empire, to reveal its areas of use and to provide a general perspective on sheepskin production. The study covers the period between 1650 and 1800 and is based on documents obtained from the General Directorate of State Archives, İSAM publications, copyrighted works and articles.

Osmanlı Devleti, ordunun lojistik ihtiyacını karşılamak, askeri gereksinimler için kaynak üretmek ve mevcut kaynakları korumak amacıyla büyük bir çaba harcamıştır. Bu bağlamda Osmanlı savunma sisteminin önemli bir unsuru olan barut ve barutun muhafazası için gerekli baruthaneler büyük öneme sahiptir. Koyun derisi, Osmanlı Devleti’nde çeşitli kullanım alanları ile özellikle barutun muhafazasında dikkat çeker. Bunun yanısıra gemilerin daha dayanıklı hale getirilmesi, devlet yazışmalarında evrakın korunması ve ciltlenmesi, günlük hayattaki eşyaların yapımı gibi amaçlarla da kullanılmıştır. Ancak koyun deri imalatı oldukça zahmetli bir süreç olup sadece merkezi bölgelerde üretilmiş ve ihtiyaç duyuldukça belirli ücretler karşılığında temin edilmiştir. Bu çalışmanın amacı, özelde koyun derisi genel olarak da koyun derisinin Osmanlı Devleti’ndeki yerini incelemek, kullanım alanlarını ortaya koymak ve koyun derisi üretimi hakkında genel bir bakış açısı sunmaktır. Çalışma 1650 ve 1800 yılları arasındaki dönemi kapsamakla birlikte ana kaynak olarak Devlet Arşivleri Genel Müdürlüğü’nden temin edilen vesikalar, İSAM yayınları, telif eser ve makalelerden yararlanılarak hazırlanmıştır.
Osmanlı Devleti’nin Barut Muhafazasında Koyun Derisi
Keywords: Early Modern Ottoman History; Yeniçağ Osmanlı Tarihi